Effect of stocking density on growth and survival of hatchery reared fry of Asian seabass, Lates calcarifer (Bloch) under captive conditions - Mojjada, Suresh Kumar; Dash, Biswajit; Pattnaik, Phaluguni; Anbarasu, M.; Joseph, Imelda (Indian Journal of Fisheries, 2013)
One of the important factors determining the success in open sea floating cage farming is the availability of quality seeds of appropriate size. The commercially available hatchery produced seeds should be further reared to appropriate size before stocking in the sea cages. The Asian seabass, Lates calcarifer is an important candidate species for open sea floating cage culture. Availability of seeds of required size is an important bottleneck in the sea farming of this species. To address this issue, an experiment was conducted in 2007 off Visakhapatnam coast of India in the Bay of Bengal, to study the effect of different stocking densities on the growth and survival rate of hatchery reared seabass fry. Asian seabass fry with a mean total length of 23.9 Â±3 mm and mean body weight of 0.45Â±0.05 g were stocked in 5 t FRP tanks with 3.5 t of filtered seawater, at three different stocking densities viz., 1000, 1500 and 2000 nos. m-3 in triplicate. The fishes were fed with commercial dry pellet feed (Godrej) at 6-8% of fish biomass. Feeding was done 6 times daily at 4 h intervals . The water quality parameters were monitored and maintained within the favorable ranges for seabass culture. The growth and survival under different stocking densities were monitored for a period of 90 days. Results observed from these experimental trials showed that the specific growth rate (SGR) was inversely proportional to that of the stocking density (p<0.05), and no significant variation was noticed in the survival rate. An overall biomass production of 1.11 kg day-1 was obtained at a high stocking of 2000 nos. m-3. The results of the experiment indicated that these high stocking density techniques with proper feeding and water quality management can be used to produce large numbers of seabass fingerlings of stockable size for open sea cage culture.